PENGARUH KINERJA INDIVIDUAL DAN KEMAMPUAN TEKNIK PERSONAL PADA EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DENGAN PENDIDIKAN DAN PELATIHAN SEBAGAI PEMODERASI - Ni Putu Ayu Kusumawati; Putu Cita Ayu (UNHI Press, 2019)
Effectiveness of Accounting Information Systems is a system that is able to produce quality information and has been in accordance with the company's objectives in the use of the SIA.This research was conducted on LPD in Kediri District, with the number of observations as many as 63 samples obtained by purposive sampling method. The data analysis technique used is the residual test. Individual Performance Variables have a positive coefficient of 0.458 with a significance value of 0.000 <0.05 which means Individual Performance has a positive effect on the Effectiveness of Accounting Information Systems. Hypothesis 1 in this study was accepted. The Personal Engineering Capability variable has a positive coefficient of 0.258 with a significance value of 0.045 <0.05, which means that the Personal Engineering Capability has a positive effect on the Effectiveness of Accounting Information Systems. Hypothesis 2 in this study was accepted. The moderating variable (KI and PP) has a positive coefficient of 0.037 with a significance value of 0.773> 0.05. This shows that there is no interaction between Individual Performance and Training Education in influencing the Effectiveness of Accounting Information Systems. Hypothesis 3 in this study was rejected. Moderating variables (KTP and PP) had a positive coefficient of 0.085 with a significance value of 0.508> 0.05. This shows that there is no interaction between Personal Engineering Capabilities and Training Education in influencing the Effectiveness of Accounting Information Systems. The hypothesis 4 in this study was rejected. This shows that the higher the individual performance and personal technical abilities, the effectiveness of the accounting information system will also increase. Whereas education and training do not strengthen the positive relationship between individual performance and personal technical ability to the effectiveness of accounting information systems. For SIA to be effective, individual performance and personal technical abilities must be improved so that individuals who have good performance and competency are required to operate the system. and implement accounting information systems effectively.